2020
DOI: 10.3847/1538-4357/ab672b
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Revisit of the Relationship between the Total Field Strength and the Volume Density of Interstellar Clouds

Abstract: The Zeeman effect has been the only method to directly probe the magnetic field strength in molecular clouds. The Bayesian analysis of Zeeman measurements carried out by Crutcher et al. is the only reference for cloud magnetic field strength. Here we extended their model and Bayesian analysis of the relation between field strength (B) and volume density (n) in the following three directions based on the recent observational and theoretical development. First, we take R, the observational uncertainty of n, as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 23 publications
0
32
0
Order By: Relevance
“…values for the mass-to-flux ratio for pre-stellar objects are often close to the critical value and have large uncertainties (Soam et al 2018;Beltrán et al 2019). Concerns have also been raised about the reliability of magnetic field strengths measured via the Zeeman effect and their relation to the gas density, due to assumptions about the abundance of the OH molecule (Tassis et al 2014) and the statistical methods employed (Tritsis et al 2015;Jiang, Li & Fan 2020).…”
mentioning
confidence: 99%
“…values for the mass-to-flux ratio for pre-stellar objects are often close to the critical value and have large uncertainties (Soam et al 2018;Beltrán et al 2019). Concerns have also been raised about the reliability of magnetic field strengths measured via the Zeeman effect and their relation to the gas density, due to assumptions about the abundance of the OH molecule (Tassis et al 2014) and the statistical methods employed (Tritsis et al 2015;Jiang, Li & Fan 2020).…”
mentioning
confidence: 99%
“…Besides that, the ρ 0 derived by [3] is much lower than the value from simulations, as discussed in Section 2.2. The authors in [5] found that some parameters in the Bayesian analysis performed by [3] were overly restricted. The most important is the uncertainty of ρ, which was fixed within a factor of two (R = 2) by [3].…”
Section: Bayesian Analysismentioning
confidence: 99%
“…A smaller BIC value is preferred. Our simple modifications [5] reduced the BIC of the model of [3] by more than 100.…”
Section: Bayesian Analysismentioning
confidence: 99%
See 2 more Smart Citations